Rochen-Duvigneaud syndrome with nasopharyngeal carcinoma - Sreenath, Sarada; George, Saju Kuttiplakal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Nasopharyngeal carcinoma is an uncommon head and neck malignancy which can rarely present with cranial nerve palsies. Here we report a case of nasopharyngeal mass which presented initially with ophthalmic complaints due to compression of cranial nerves in superior orbital fissure resulting in Rochen-Duvigneaud syndrome. It was histologically proven as non keratinising differentiated type of Nasopharyngeal carcinoma